2023
DOI: 10.2147/ijn.s436940
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane Coated pH-Responsive Intelligent Bionic Delivery Nanoplatform for Active Targeting in Photothermal Therapy

Xiangyu Zhang,
Zelai He

Abstract: Aim To produce pH-responsive bionic high photothermal conversion nanoparticles actively targeting tumors for sensitizing photothermal therapy (PTT). Materials and Methods The bionic nanoparticles (ICG-PEI@HM NPs) were prepared by electrostatic adsorption of indocyanine green (ICG) coupled to polyethyleneimine (PEI) and modified with tumor cell membranes. In vitro and in vivo experiments were conducted to investigate the efficacy of ICG-PEI@HM-mediated PTT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Notably, Li et al and Zhang et al reported that PEI and PEG have no significant UV absorption peaks. 35,36 A red shift was observed at 700-800 nm for SNP/PEI-ICG@PEG, which could be attributed to the strong binding of ICG within the polymer core. The presence of an absorption peak near 808 nm for SNP/PEI-ICG@PEG confirmed its potential for both PTT and PDT upon laser excitation at this wavelength.…”
Section: Characterization Of Various Nanoparticlesmentioning
confidence: 98%
“…Notably, Li et al and Zhang et al reported that PEI and PEG have no significant UV absorption peaks. 35,36 A red shift was observed at 700-800 nm for SNP/PEI-ICG@PEG, which could be attributed to the strong binding of ICG within the polymer core. The presence of an absorption peak near 808 nm for SNP/PEI-ICG@PEG confirmed its potential for both PTT and PDT upon laser excitation at this wavelength.…”
Section: Characterization Of Various Nanoparticlesmentioning
confidence: 98%
“… 38–40 Thus, the developed drug delivery system achieves dual-targeting of glioblastomas and brain vascular endothelial cells. Upon reaching the tumor site and subsequent exposure to 808 nm laser irradiation, ICG induces effective hyperthermia, 41 , 42 facilitating localized thermal therapy and triggering the burst release of SN38. The released SN38, by inhibiting DNA topoisomerase, induces tumor cells apoptosis, thereby realizing the synergistic effects of chemo-photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%